Testing the Four Factors of the Carhart Model Against Excess Return of Shares in Companies Registered in the Kompas 100 Index for the 2014-2016 Period - Delvira Mahmud (Universitas Negeri Gorontalo, 2019)
The researcher intends to test the four carhart factor model of stock excess return in companies incorporated in Kompas 100 for the 2014-2016 period. Regression analysis was performed on four carhart factor models, namely market returns, firm size, book to market, and momentum towards excess return. The results of this study indicate that in the partial hypothesis testing market return, firm size, and book to market equty variables significantly influence the excess return, while the momentum variable does not significantly influence the magnitude of excess return.Keywords: Four factors, market returns, firm size, book to market equity, momentum, excess stock returns